BIOAKUMULASI LOGAM BERAT Cu OLEH Bacillus sp - Riesta Primaharinastiti; A. Toto Poernomo; Noor Erma S. (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
The research was conducted to investigate the ability of Bacillus sp in accumulating Cu and how much it can be acumulated. The medium used to growth the bacterium was Nutrient Broth and Atomic Absorption Spectrophotometry methods was used to assay the Cu, both in the cells and medium. The result of this study showed that Bacillus sp incubated in the Nutrient Broth medium containing 10 ppm of Cu, with continuous stirring in the room temperature was able to reduce Cu in the medium 8.912–12.623% and accumulate Cu in the cell 0.1149–0.1400 %/mg cells. Based on this result, it is necessary to develop more studies to find out what factors that influence the accumulation process and to optimize the bioprocess.